2013
DOI: 10.1021/nl304365e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Strong-Field Photoemission from Plasmonic Nanoparticles

Abstract: We demonstrate the ultrafast generation of electrons from tailored metallic nanoparticles and unravel the role of plasmonic field enhancement in this process by comparing resonant and off-resonant particles, as well as different particle geometries. We find that electrons become strongly accelerated within the evanescent fields of the plasmonic nanoparticles and escape along straight trajectories with orientations governed by the particle geometry. These results establish plasmonic nanoparticles as versatile u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
242
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 263 publications
(253 citation statements)
references
References 35 publications
(83 reference statements)
9
242
2
Order By: Relevance
“…Hundreds of nJ were demonstrated experimentally ( [6] and this work), and our concept can be combined with divided-pulse approaches [11]. Perceived applications range from ultrafast electron diffraction with single-electron pulses at MHz repetition rates [12,13] to various experiments in ultrafast plasmonics performed with long-cavity oscillators [14]. Many other fields of research may also benefit from the mechanisms and perspectives reported here.…”
mentioning
confidence: 78%
“…Hundreds of nJ were demonstrated experimentally ( [6] and this work), and our concept can be combined with divided-pulse approaches [11]. Perceived applications range from ultrafast electron diffraction with single-electron pulses at MHz repetition rates [12,13] to various experiments in ultrafast plasmonics performed with long-cavity oscillators [14]. Many other fields of research may also benefit from the mechanisms and perspectives reported here.…”
mentioning
confidence: 78%
“…In this regime, the quantum nature of the interaction opens a new paradigm for utilizing optical gap antennas beyond the control of electromagnetic fields at the nanometer length scale [16,17]. For instance, incoming photons can exchange energy with tunneling charges modifying thus the conductance of the barrier [18,19] and strong-field effects were recently reported [20,21]. Therefore, adopting metal-based optical antennas as a disruptive technological vehicle may provide advanced functional devices to interface nanoscale electronics and photonics.…”
Section: Optical Rectificationmentioning
confidence: 99%
“…051401 Recent advances in nanoscience and nanotechnologies are creating new avenues for designing and making nanometerscale metal structures which respond to irradiation with electromagnetic radiation by creating a tunable induced electric field near the metal surface [1,2]. This induced "plasmonic" field originates in the incident-field-driven coherent collective motion of conduction electrons which, when stimulated near its natural resonance (plasmon) frequency, generate a very large induced polarization in subwavelength-size structures on substrate surfaces [3][4][5][6][7][8][9] and isolated nanoparticles [10]. Near metallic nanospheres and for linearly polarized incident radiation [10][11][12][13][14][15][16], the oscillating induced polarization gives rise to oscillating plasmonic fields with dipole-like angular distribution oriented along the polarization direction of the incident radiation [17].…”
mentioning
confidence: 99%